Role of transformational leadership in enhancing followers’ psychological empowerment - Nurshahira Ibrahim; Azman Ismail; Munirah HanimYusuf; Siti Ngayesah Ab. Hamid (2016)
According to recent literature on organizational leadership, the ability of leaders to implement a transformational process appropriately may lead to enhanced followers’ psychological empowerment in organizations. Although this relationship is significant, the role of transformational leadership as an important predicting variable has not been given sufficient emphasis in the organizational leadership model. Therefore, this study was conducted to investigate the relationship between transformational leadership and followers’ psychological empowerment using 86 usable questionnaires gathered from employees at a multinational company in Sarawak, Malaysia. The results of the SmartPLS path model analysis confirm that idealized influence, individualized consideration, and intellectual stimulation act as important predictors of followers’ psychological empowerment. Additionally, discussion, implications and conclusion are presented in detail.